Heteroleptic Ir(iii) phosphors with bis-tridentate chelating architecture for high efficiency OLEDs1. Issue 14 (14th April 2015) - Tong, Bihai; Ku, Hsiao-Yun; Chen, I.-Jen; Chi, Yun; Kao, Hao-Che; Yeh, Chia-Chi; Chang, Chih-Hao; Liu, Shih-Hung; Lee, Gene-Hsiang; Chou, Pi-Tai
<x xml:space="preserve">Abstract</x> Emissive Ir(iii) complexes bearing two tridentate chelates were synthesized. The multiple coordination mode of the chelate warrants a new class of metal-based phosphors for OLED applications.